THE EFFECT OF EDUCATION AND TRAINING ON THE QUALITY OF MANAGERIAL DECISION MAKING WITH FINANCIAL MANAGEMENT PERFORMANCE AS AN INTERVENING VARIABLE (Study on Regional Device Organization in Palu City) - Ahmad Fauzi Yetta; Muh. Dzulkifli; Andi Atira; Abdul Pattawe; Ernawaty Usman; Jurana N.S (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to highlight the influence of education and training on the quality of managerial decision-making through the performance of financial managers as an intervening variable. This study uses a quantitative method with a survey research design. The sample in this study was the Regional Apparatus Organization (OPD) of Palu City with a total of 41 respondents. The sample was taken based on a census technique in this study population. The data analysis technique used was Partial Least Square with the help of the WarpPLS program version 7.0. The results of this study indicate that the education variable has an influence but is not significant on the quality of managerial decision-making. Meanwhile, the training and performance variables of financial managers have a positive and significant effect on the quality of managerial decision-making, education and training have a positive and significant effect on the quality of managerial decision-making and financial manager performance mediates the relationship between education and training on the quality of managerial decision-making.